Vinegar elaboration using waste from banana, camu camu, cocona, carambola, cane sugar juice and ají charapita - Vicente Santa Cruz, Edgar (2023)
The Ucayali region (Peru) is characterized by a great variety of fruits, which are often not used generating waste. These wastes can used by making products such as vinegar. The main objective of this research was to take advantage of the fruit residues of the area: banana, cocona, carambola, camu camu, chili charapita as well as sugar cane juice in the preparation of vinegar. For this, three initial mixtures were made with different proportions of fruits. In the first stage, a control of the alcoholic fermentation (temperature, pH, density) was carried out, using Sacharomyces cerevisiae yeast, evaluating the final alcoholic strength. In the second stage, the control of the acetic fermentation was carried out, using a mother vinegar based on Acetobacter aceti, evaluating the final acetic acidity and the residual alcohol. The best treatments went to a sensory evaluation by a panel (regular consumers) selecting the best based on overall acceptability. The best treatment was that of the mixture that contained a higher percentage of banana and carambola. This treatment also met the requirements for a commercial vinegar, so it was feasible to use these fruit residues in the preparation of vinegar.